DYNAMIC MODEL OF THE TEST BENCH FOR HELICOPTER VANES LONGERONS - I.V. BOGDANOVA; А.D. LUKJANOV; S.А. SHAMSHURA (Advanced Engineering Research)
The dynamic model of the test bench for helicopter vanes longerons are described and studied in the paper. Model was developed to determining a vibration level, which pass to ambient space. The global aim of presented work - to optimize the vibroprotection of dynamic test bench.